The science of construction materials - Freiesleben Hansen, Per. (Springer Berlin Heidelberg :, 2009)
The Science of Construction Materials is a study and work book for civil engineering students. Since the contents of the book are presented in a way that makes the reading an active process, the book is also suitable as self-study for the researcher and practising civil engineer. The publication is not a textbook on thermodynamics, but rather an incentive to use the calculation methods of physical chemistry to solve problems within the science of construction materials. The presentation of the theoretical subjects is supported by approximately 500 exercises with solutions as well as commented examples of calculations; throughout the book the relation to civil engineering practice is demonstrated. A detailed subject index and a comprehensive collection of tables of physical and chemical data for substances relevant for the science of construction materials are also found in the book. This makes the book suitable as a work of reference. "Many of the aspects of the deterioration of concrete infrastructure, such as corrosion of reinforcing steel, cannot be addressed until the underlying physics and chemistry are clearly understood. The textbook, Science of Construction Materials, is the first one in English that synthesizes various materials science issues, which are the foundation of our recent advances in infrastructure materials. An unusual and critically important aspect of the textbook is that it includes not only detailed concepts of thermodynamics and electrochemistry but also lays a mathematical foundation of computational models, which are necessary to tackle complex interactions between chemistry and mechanics. This book fills a much-needed gap in the scant literature available to students and researchers trying to learn the science of infrastructure materials." Surendra P. Shah, Walter P. Murphy Professor of Civil Engineering, Director of the Center for Advanced Cement Based Materials, Northwestern University . Systems of matter -- Thermodynamic concepts -- First law -- Second law -- Calculations of equilibrium -- Electrochemistry -- Mathematical appendix -- Tables -- Solutions to check-up questions and exercises.